(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The role of Armidallidium vulgare as a pest of fruits both of Cucurbita melo var. inodorus and C. pepo cv "genovese" has been observed through several years, in Sicily (Palermo and Trapani departments). With regard to the former cultivation, the highest percentages of infestation always interested those cv with ribbed peel, much less on cv smooth skin. With respect to marrows, the highest percentages of attacks due to the isopoda was 8,47%, through the years 2004, 2005; on 2006 such a percentage reached to 15% about.